EFFECTIVENESS AND EFFICIENCY OF BOAT LIFT NET WITH THE ADDITION OF LED FISH TOOLS IN BONE DISTRICT - Imran, Imran; Rahmatang, Rahmatang; Tandipuang, Paduartama (Politeknik Kelautan dan Perikanan Dumai, 2023)
Success in operating the boat lift net fishing gear is influenced by many factors, one of which is the light tool as a fish attractant. This research conducted trials on adding fish LED aids to the gouging of the boat lift net while the mercury lamp power was reduced. This was done to see to what extent the addition of LED fish aids impacted the effectiveness and efficiency of the boat lift net. Therefore, this research aims to determine the effectiveness and efficiency of boat lift net with the addition of fish LED aids. In collecting data, the methods used were experimental and interview methods. The research results show that the addition of fish LED aids can increase the effectiveness value of the pry chart, namely 112.39% compared to the control boat lift net. The operation of the boat lift net is also more efficient with the installation of fish LED aids. This can be seen from the greater number of catches produced on the boat lift net fitted with fish LED aids even though the mercury lamp power was reduced.